2020
DOI: 10.1186/s12876-020-01243-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating total bile acid levels were associated with organ failure in patients with acute pancreatitis

Abstract: Background: Recent studies have shown that bile acids (BAs) are closely related to metabolic and inflammatory diseases. Our study aimed to investigate whether circulating total bile acid (TBA) levels were associated with the severity of acute pancreatitis (AP). Methods: We retrospectively collected data on patients diagnosed with AP in a tertiary center from 01 January 2014 to 31 December 2016. The highest TBA value during the first 1,2,3,5,7 days after admission was determined as D1, D2, D3, D5, D7 TBA max. P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Bile acids are associated with risk factors of pancreatic adenocarcinoma, such as obesity, diabetes, pancreatitis, and hypertriglyceridemia. For example, the concentration of DCA is elevated in type 2 diabetes [92], ob/ob mice have elevated plasma bile acid levels [93], and circulating total bile acid levels are increased in pancreatitis [94].…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are associated with risk factors of pancreatic adenocarcinoma, such as obesity, diabetes, pancreatitis, and hypertriglyceridemia. For example, the concentration of DCA is elevated in type 2 diabetes [92], ob/ob mice have elevated plasma bile acid levels [93], and circulating total bile acid levels are increased in pancreatitis [94].…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol concentration predicts the effect of plasmapheresis on hypertriglyceridemic AP 8 . Increased circulating total bile acid levels were associated with organ failure in patients with AP 9 . There are no studies investigating e cacy of MCH, MCV, MCHC, HGB or RBC in predicting length of hospital stay of AP.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the disease-exacerbating effect of BAs would not only require reflux into the pancreatic duct but could be elicited by serum or interstitial BAs in jaundice patients [85]. In addition, systemically circulating BAs also contributed to organ failure in pancreatitis patients [86]. Furthermore, a recent study in mice suggested a strong association between chronic pancreatitis and gut microbiota [87].…”
Section: Bile Acids and Pancreasmentioning
confidence: 99%